2012
DOI: 10.1016/j.rgg.2012.05.010
|View full text |Cite
|
Sign up to set email alerts
|

Variations of the geomagnetic field during the Cretaceous

Abstract: This study provides a compilation of the paleointensity records for the Cretaceous period derived from sediments of the Russian Plate and adjacent areas. The paleoinetensity values were calibrated using the laboratory redeposition experiments. Remarkable differences in the relative paleointensity variations were detected at the Berriasian–Early Barremian, Late Barremian–Santonian and Early–Late Maastrichtian boundaries. In the Berriasian–Early Barremian interval, the paleointensity varied stochastically, with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
0
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 15 publications
2
0
0
Order By: Relevance
“…4b). Earlier, we studied these deposits on the example of the Crimea deposits (Kurazhkovskii et al, 2012). The study by described in Kurazhkovskii et al (2012) as well as the present study it revealed that significant bursts of paleointensity took place in the end of the Maastrichtian.…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…4b). Earlier, we studied these deposits on the example of the Crimea deposits (Kurazhkovskii et al, 2012). The study by described in Kurazhkovskii et al (2012) as well as the present study it revealed that significant bursts of paleointensity took place in the end of the Maastrichtian.…”
Section: Discussionsupporting
confidence: 68%
“…Earlier, we studied these deposits on the example of the Crimea deposits (Kurazhkovskii et al, 2012). The study by described in Kurazhkovskii et al (2012) as well as the present study it revealed that significant bursts of paleointensity took place in the end of the Maastrichtian. In addition, the burst of the paleointensity in the end of the Selandian was detected both on sediments of borehole and on the deposits of lower Volga (Fig.…”
Section: Discussionsupporting
confidence: 68%